2021
DOI: 10.1007/s10519-021-10081-9
|View full text |Cite
|
Sign up to set email alerts
|

Gene-by-Crisis Interaction for Optimism and Meaning in Life: The Effects of the COVID-19 Pandemic

Abstract: The corona virus disease 2019 (COVID-19) pandemic and the restrictions to reduce the spread of the virus has had a large impact on daily life. We investigated the individual differences in the effect of the COVID-19 pandemic and first lockdown on optimism and meaning in life in a sample from the Netherlands Twin Register. Participants completed surveys before (N = 9964, Mean age: 48.2, SD = 14.4) and during the first months of the pandemic (i.e. April–May 2020, N = 17,464, Mean age: 44.6 SD = 14.8), with a sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 55 publications
4
9
0
Order By: Relevance
“…However, the Twins Early Development Study on adult twins in Great Britain did show that the first month of lockdown did not result in major changes in the genetic or environmental origins in psychological or attitudinal traits compared to a pre-pandemic timepoint [ 31 ]. A similar observation was made by the Netherlands Twin Register , they did not find a significantly altered heritability for well-being related outcomes before and after the start of the pandemic [ 32 ]. Both these studies support the explanation that the increase in the contribution of genetics that we observe is a consequence of the ongoing pandemic rather than a slow return to a pre-pandemic situation.…”
Section: Resultssupporting
confidence: 70%
“…However, the Twins Early Development Study on adult twins in Great Britain did show that the first month of lockdown did not result in major changes in the genetic or environmental origins in psychological or attitudinal traits compared to a pre-pandemic timepoint [ 31 ]. A similar observation was made by the Netherlands Twin Register , they did not find a significantly altered heritability for well-being related outcomes before and after the start of the pandemic [ 32 ]. Both these studies support the explanation that the increase in the contribution of genetics that we observe is a consequence of the ongoing pandemic rather than a slow return to a pre-pandemic situation.…”
Section: Resultssupporting
confidence: 70%
“…Contrary to conventional wisdom, meta-analyses (Aknin et al, 2022;Prati & Mancini, 2021) reported that the overall impact has been small in magnitude but complex and that it has depended on the rigidity of containment measures, the stage of the pandemic, and the direct experience of the disease. Furthermore, the pandemic induced heterogeneous psychological responses as the result of unequal resources and differences in genetic sensitivity to environmental shocks (de Vries et al, 2022). Interestingly, Recchi et al (2020) found an unexpected increase in subjective well-being (measured as the self-assessed frequency with which respondents had feelings of nervousness or relaxation, sadness or happiness, etc.)…”
Section: The Socioemotional Paradox Of the Covid-19 Pandemicmentioning
confidence: 99%
“…If an environmental exposure comprises a limited number of classes, GxE can be investigated by comparing heritability estimates across different environments. One study looked at optimism and meaning of life before and during the COVID-19 pandemic 52 . A gene-by-crisis interaction model showed slightly lower heritability estimates for these traits during the first months of the pandemic and lower than unity genetic correlations across time (.75 and .63) implying GxE, with different genes influencing optimism and meaning in life before and during the pandemic.…”
Section: Gene -Environment Interactionmentioning
confidence: 99%